2014
DOI: 10.5194/bg-11-4627-2014
|View full text |Cite
|
Sign up to set email alerts
|

A fine fraction of soil used as an aerosol analogue during the DUNE experiment: sequential solubility in water, decreasing pH step-by-step

Abstract: Abstract.A soil sample collected in a desert aerosol source area near Douz (southern Tunisia) was dry-sieved at 20 µm in order to extract the fraction similar to a wind-generated aerosol, and was used to seed mesocosms during the DUNE experiment (a DUst experiment in a low Nutrient, low chlorophyll Ecosystem). In this work, said "aerosol-like" fine dust was sequentially leached by short contacts with water at initial pHs, decreasing from seven to one, representing various wet environmental conditions. For each… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Indeed, anthropogenic metals are largely more soluble than metals issued from desert dust 40 (Desboeufs et al, 2005). However, the solubility values obtained in our dust addition experiments for Al and Fe are in agreement with the values found in ultrapure water for the same amended dust (Aghnatios et al, 2014), for other analogs of Saharan dust (Desboeufs et al, 2001;Paris et al, 2011) or for dust collected over Sahara (Paris et al, 2010).…”
supporting
confidence: 90%
“…Indeed, anthropogenic metals are largely more soluble than metals issued from desert dust 40 (Desboeufs et al, 2005). However, the solubility values obtained in our dust addition experiments for Al and Fe are in agreement with the values found in ultrapure water for the same amended dust (Aghnatios et al, 2014), for other analogs of Saharan dust (Desboeufs et al, 2001;Paris et al, 2011) or for dust collected over Sahara (Paris et al, 2010).…”
supporting
confidence: 90%
“…Saharan dust is a major source of particles in the Mediterranean (D'Almedia, 1986;Loÿe-Pilot et al, 1986) and does have an impact on the regional climate system (Nabat et al, 2012(Nabat et al, , 2015. The literature on Mediterranean aerosols is often centered on Saharan dust deposition, which is believed to have the largest impact on the basin's biogeochemistry (e.g., Bergametti et al, 1992;Migon and Sandroni, 1999;Aghnatios et al, 2014). This study provides the first Mediterranean assessment of the contribution of another source of atmospheric phosphate than dust.…”
Section: Discussionmentioning
confidence: 96%
“…The impacts of aerosol deposition on the Mediterranean region are not fully understood and they may change in the future as a result of climate change impacts on land and sea (e.g., Peñuelas et al, 2013). The Sahara and Middle East are important sources of natural lithogenic dust (e.g., Ganor and Mamane, 1982;Bergametti et al, 1989;Al-Momani et al, 1995;Vincent et al, 2016), whereas the surrounding cities and highly industrialized areas are sources of atmospheric pollutants emitted by biofuels for heating and fossil fuel burning (Migon et al, 2001;Piazzola et al, 2016). The 85 million hectares of forests around the basin associated with the Mediterranean dry summer climate are also an occasional intense aerosol source due to wildfire emissions (Kaskaoutis et al, 2011;Poupkou et al, 2014;Turquety et al, 2014), providing for instance soluble iron to the Mediterranean (Guieu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of dry deposition in high-elevation environments, dissolved constituents are typically obtained by rinsing buckets with 1 L of ultrapure water and filtering the slurry through glass fiber filters (Grant & Lewis, 1982;Mladenov et al, 2009;Morales-Baquero et al, 2006). Other studies of solute leaching from dust in seawater (Herut et al, 2002) and artificial dust aerosols in water at different pH values (Aghnatios et al, 2014) use much lower water volumes (30 mL and 100 mL, respectively) for extraction. Contact times between ultrapure water and dust or other dry constituents may be instantaneous (Aghnatios et al, 2014) or as long as 30 h (Herut et al, 2002) but are often rarely reported.…”
Section: 1002/2016jd026416mentioning
confidence: 99%
“…Other studies of solute leaching from dust in seawater (Herut et al, 2002) and artificial dust aerosols in water at different pH values (Aghnatios et al, 2014) use much lower water volumes (30 mL and 100 mL, respectively) for extraction. Contact times between ultrapure water and dust or other dry constituents may be instantaneous (Aghnatios et al, 2014) or as long as 30 h (Herut et al, 2002) but are often rarely reported. Techniques for extracting water-soluble constituents in our study were intended to simulate rapid movement of particulates along hydrologic flow paths during snowmelt.…”
Section: 1002/2016jd026416mentioning
confidence: 99%